Pattern of birth control among married women in the rural village of San Joaquin, Iloilo. - Santiagudo, Jocelyn Toriado (2008.)
The study is conducted to know the pattern of birth control among married women. The study further aims to identify the different birth control methods practiced by married women in the rural community, specifically in relation to women's age, educational attainment and the number of children that they have. The study found out that the respondents derived a quite a number of benefits for using birth control, of which two major reasons are birth-spacing and end bearing. The practice of birth control during reproductive stage, provide women with otherjob opportunities and lifestyle choices, aside from the confines of home and family. But then, other considerations are recommended for this study to come up with better outcomes for future research regarding birth control practice.
Research Project (Undergraduate, Bachelor of Arts in Community Development-Sociology) College of Arts and Sciences, UP Visayas, Miagao, Iloilo
Keywords: Birth control